2020
DOI: 10.3390/polym12040848
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance of Indacenodithiophene-Benzothiadiazole Copolymer Containing Polar Side Chains and Single Wall Carbon Nanotubes Composites

Abstract: Composite films of indacenodithiophene-bezothiadazole copolymers bearing polar side chains (P1) and single wall carbon nanotubes (SWCNTs) are found to show a competitive thermoelectric performance compared to their analogous polymers with aliphatic side chains (P2). The enhanced power factors could be attributed to the stronger interfacial interactions between the P1/SWCNTs compared to that of P2/SWCNTs containing the same ratio of SWCNTs. A maximum power factor of 161.34 μW m−1 K−2 was obtained for the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…IDT-based polymers have been widely used in organic field effect transistor (OFET) and solar cell applications [ 29 , 30 , 31 ]; however, although research on its TE properties has also been reported [ 32 , 33 ], the TE performance is still very low, and the detailed structure–property relationships are not comprehensive. In addition, we have recently reported IDT-based composite thermoelectric materials and found that the composites showed good performance with power factor of 161.34 mW/m −1 K 2 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…IDT-based polymers have been widely used in organic field effect transistor (OFET) and solar cell applications [ 29 , 30 , 31 ]; however, although research on its TE properties has also been reported [ 32 , 33 ], the TE performance is still very low, and the detailed structure–property relationships are not comprehensive. In addition, we have recently reported IDT-based composite thermoelectric materials and found that the composites showed good performance with power factor of 161.34 mW/m −1 K 2 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is strong evidence that this polymer (which bears only alkyl side chains) does not disperse s-SWCNTs at all. In contrast, PNDITEG-AT-C 10 (which bears a polar ethylene glycol side chain on the NDI moiety) readily disperses (wraps) s-SWCNTs, which we ascribe to the enhanced π–π interaction between s-SWCNT and polymers bearing polar side chains for the reasons described above. As has been shown in previous work, , increasing the length of alkyl side chains can enhance the binding energy between conjugated polymers and SWCNTs by enlarging the contact surface. Indeed, PNDITEG-AT-C 12 , which bears both polar side chains and lengthened alkyl side chains, produced the highest density of s-SWCNTs from the as-obtained inks, as indicated in Figure a.…”
Section: Resultsmentioning
confidence: 56%
“…[39] Along similar lines, several research groups explored the relationship between the polymer structures and the resulting thermoelectric properties. [40][41][42][43][44] In this work a) we synthesized novel D-A copolymers based on DPP and EDOT in varying proportions (Figure 1) to tailor solid-state microstructures and electronic structures to achieve high electrical conductivity, excellent thermal, electrical, and air stability and to overcome the bottlenecks associated poor processability as discussed earlier, and b) we carried out a systematic investigation of the ability a Lewis-acid dopant B(C 6 F 5 ) 3 and its pre-formed adducts of the type "conjugated molecule": B(C 6 F 5 ) 3 to serve as dopants for our novel conductive polymers, as an extension of our previous study. [45] Here, the conjugated molecule is an oligomer resembling the repeat unit of the polymer (Figure 2) as opposed to our previous work where the "oligomer" was more arbitrarily selected.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ] Along similar lines, several research groups explored the relationship between the polymer structures and the resulting thermoelectric properties. [ 40–44 ]…”
Section: Introductionmentioning
confidence: 99%